Factors Associated with the Occurrence of Cyanotic Spells in Tetralogy of Fallot Patients - Teddy Ontoseno (Paediatrica Indonesiana, 1995)
A study was carried out on 114 tetralogy of Fallot patients attending the Department of Child Health, Medical School, University of Airlangga/Dr. Soetomo Hospital between 1 January 1988 to 31 December 1992. Only 81 patients fulfilled our study criteria where 52 (64.2'%) were cases with complications such as cyanotic spells, 4 (4 .93%) among them had brain abscesses. Twenty-nine individuals without complications acted as controls. Age, sex, nutritional status, hematocrit, MCHC and onset of symptoms between the two groups were analyzed using the multiple regression logistic. It has been shown that relative anemia, polycythemia and the age of 2-5 years contributed to the onset of cyanotic spells, respectively, R = 0.3171 and p = 0 .0004; R = 0.2220 and p = 0 .0073; R = 0.1363 and p = 0.00465. Therefore, in conventional treatment of tetralogy of Fallot patients it is essential to observe these risk factors in order to avoid complications and to improve the quality of life in these patients who are on the waiting list for surgery.